Multiplex SERS Phenotyping of Single Cancer Cells in Microdroplets. Issue 1 (14th November 2022) - Oliveira, Kevin; Teixeira, Alexandra; Fernandes, José M.; Lopes, Cláudia; Chícharo, Alexandre; Piairo, Paulina; Wu, Lei; Rodríguez‐Lorenzo, Laura; Diéguez, Lorena; Abalde‐Cela, Sara
Abstract: In the context of personalized medicine, the analysis of single cells is key in order to understand the origin and evolution of cancer to provide an accurate prognosis. Microfluidics and microdroplets are increasingly used for the handling and understanding of the behavior of single cells, as they offer the perfect isolated environment. However, due to the small volumes handled, it is necessary to couple this technology with an ultrasensitive detection technique. Herein, surface‐enhanced Raman scattering (SERS) spectroscopy and droplet microfluidics are combined toward the multiplex phenotypic analysis of single cancer cells. For this, cancer cells are labeled with different SERS tags that recognize membrane proteins and encapsulated individually in microdroplets. Afterward, single cells within microdroplets are imaged by SERS spectroscopy. To the best of the authors' knowledge, this is the first time that a multiplex phenotypic SERS analysis of single cells in microdroplets is shown. This integrated optofluidic platform paves the way toward the multiplex and automated characterization of cell populations in cancer patients. Abstract : In the context of personalized medicine, the analysis of single cells is key to understand the origin and evolution of cancer to provide an accurate prognosis. Herein, the multiplex phenotypic surface‐enhanced Raman scattering analysis of single cells in microdroplets is presented. This integrated optofluidic platform paves the way toward the multiplex and automated characterization of cell populations from cancer patients.